Fjällräven i ett föränderligt klimat - Marander, Emma (SLU/Dept. of Animal Environment and Health (until 231231), 2022)
Climate change is an ongoing threat to the world´s biodiversity, and has an alarming effect on the Arctic. One species that can only be found in this particular habitat is the arctic fox, whose future is threatened by the aversive effects of global warming. The aim of this study was to investigate how climate change is affecting the arctic fox. A literature review of current research was done to identify relevant scientific information concerning the process of climate change affecting the species. Recent data indicates that the life of the arctic fox will be affected in many different aspects. The sea ice is decreasing, and this change is expected to continue, which affects both the arctic fox gene flow but also the abundance of marine food resources. The boreal forest is also expected to expand further north, leading to a shrinking tundra, as well as an influx of predators migrating from the south. The red fox, which has already significantly affected the Fennoscandian arctic fox population, is expected to further expand its distribution north, which will be detrimental to the prospect of survival of the arctic fox. The rodent cycles, which are a key process in the tundra ecosystem, are also expected to become more unstable. The arctic fox´s reproductive success is dependent on peaks in the rodent population and will be severely affected if these cycles fail. Many conservation measures have been taken, especially in Fennoscandia, in the form of support feeding the artic fox and controlling the red fox expansion. Conservation and management will be necessary in the future, and new research is needed to find sustainable and ethical methods for the conservation of the arctic fox. Insight into the process of converging factors is also fundamental. Even if the arctic fox is an opportunistic predator, a change in both terrestrial and marine food resources can lead to a food shortage for the arctic fox. Understanding how this, in conjunction with a shrinking tundra and a boreal invasion will impact the global arctic fox population is necessary to be able to predict and find sustainable solutions for the future.